A study of information seeking behaviour of quality assurance engineering students. - Chua, Thomas Kian Lye. (2008)
Several studies have found that the information skills of students , particularly in engineering are not satisfactory and there is need for improvement. These studies stressed that it is not the sole responsibility of the librarian or academic staff to impart these skills. It requires a collaborative effort by library and academic staff to develop and nurture a user-centred learning environment. This study looked at the information seeking behaviour of students at Ngee Ann Polytechnic. It examined the interactions between students, academic staff and librarian on information seeking and retrieval from electronics databases. The student attitude for information searching and use are assessed and recommendations are made on the various roles of staff who can impart the skills to the students through a system-based framework.